Reproducing ear-canal reflectance using two measurement techniques in adult ears - Nørgaard, Kren Monrad; Fernandez-Grande, Efren; Schmuck, Constanze; Laugesen, Søren (The Journal of the Acoustical Society of America, 2020)
Clinical diagnostic applications of ear-canal reflectance have been researched extensively in the literature, however, the measurement uncertainty associated with the conventional measurement technique using an insert ear probe is unknown in human ear canals. Ear-canal reflectance measured using an ear probe is affected by multiple sources of error, including incorrect estimates of the ear-canal cross-sectional area and oblique ear-probe insertions. In this paper, ear-canal reflectance measurements are reproduced in an occluded-ear simulator and in 54 adult ear canals using two different measurement techniques: a conventional ear probe and a two-microphone probe that enables the separation of reverse- and forward-propagating plane waves. The two-microphone probe is inserted directly into test subjects' ear canals, and the two-microphone method is distinguished by not requiring the ear-canal cross-sectional area to calculate the ear-canal reflectance. The results show a reasonable agreement between the two measurement techniques. The paper further examines the influence of oblique ear-probe insertions and the compensation for such oblique insertions, which results in an improved agreement between the two measurement techniques.